Buckling Analysis of Thin Walled Cylinder with Combination of Large and Small Stiffening Rings under External Pressure. (2015) - Zhu, Y.; Dong, J.H.; Gao, B.J.
Abstract: Although most thin walled cylinders under external pressure are stiffened by rings with the same dimension, it is believed that the combination of large and small stiffening rings is helpful to the lightweight design of structures. In this paper, eigenvalue buckling analysis has been done to study the buckling pattern (BP) and critical pressure P cr of thin walled cylinders with the combination of large and small stiffening rings. It is found that there is a map of buckling patterns for different ring combinations. Three BPs appear as buckling of cylinder together with both large and small stiffening rings (BP-I), buckling of cylinder together with small stiffening rings but without large stiffening rings (BP-II), and finally, buckling of cylinder without both large and small stiffening rings (BP-III). In the region of BP-I and BP-II, values of P cr increase with the size of large and small ring, but remain constant in the region of BP-III. And it indicates a remarkable optimization space for the design of stiffening rings. The large ring location and sizes of both large and small rings are optimized for lightweight design of the example cylinder, which yields a reasonable result satisfying the stability requirement under external pressure.